2002
DOI: 10.1029/2001ja000224
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ultralow‐frequency cavity modes using spacecraft data

Abstract: [1] The cold, magnetized plasma in the Earth's magnetosphere supports two ultralowfrequency plasma wave modes. Both these modes may exhibit resonant oscillations in the magnetosphere cavity. Theoretical and numerical studies have predicted the existence of cavity/waveguide resonance modes, yet experimental evidence is sparse. In this paper we detail the expected structure of these modes using both one dimensional (1-D) and three-dimensional (3-D) magnetohydrodynamic (MHD) numerical models. The cavity/ waveguid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(98 citation statements)
references
References 81 publications
3
93
2
Order By: Relevance
“…We should note, however, that observational evidence for global fast mode cavity resonance or waveguide mode is still very limited (Samson and Rankin, 1994;Waters et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We should note, however, that observational evidence for global fast mode cavity resonance or waveguide mode is still very limited (Samson and Rankin, 1994;Waters et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Russel and Hoppe, 1981;Yumoto et al, 1984;Takahashi et al, 1984;Engebretson et al, 1986Engebretson et al, , 1987. Contrarily, a number of investigations using numerical modelling have suggested that cavity or waveguide modes in the magnetosphere are the drivers of the FLRs (Allan et al, 1985;Samson et al, 1995;Waters et al, 2000). A few studies have also presented results in support of the observation of these fast mode resonances (FMRs) in ground-based data (Samson et al, 1995;Menk et al, 2000).…”
Section: Introductionmentioning
confidence: 60%
“…A few studies have also presented results in support of the observation of these fast mode resonances (FMRs) in ground-based data (Samson et al, 1995;Menk et al, 2000). However, direct observational evidence for FMRs in satellite data is sparse (Waters et al, 2002). Verõ et al (1998) investigated the relationship between FLRs and UWs but alluded to the possible presence of signals from another unidentified source.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations